Metabolically Healthy Obesity and Risk of Kidney Function Decline. Issue 4 (2nd March 2018) - Chang, Alex R.; Surapaneni, Aditya; Kirchner, H. Lester; Young, Amanda; Kramer, Holly J.; Carey, David J.; Appel, Lawrence J.; Grams, Morgan E.
Abstract : Objective: The aim of this study was to examine the association between BMI categories, stratified by metabolic health status, and the risk of kidney function decline (KFD). Methods: In this study, 42, 128 adult patients with a stable BMI were classified over a 3‐year baseline window by BMI and metabolic health status (assessed by Adult Treatment Panel‐III criteria). KFD was defined as an estimated glomerular filtration rate (eGFR) decline ≥ 30%, eGFR < 15 mL/min/1.73 m 2, or receipt of dialysis and/or transplant. Results: Over a median of 5.1 years (interquartile range 2.1‐8.9), 6, 533 (15.5%) individuals developed KFD. Compared with the normal weight, metabolically healthy category, metabolically healthy obesity was associated with a higher risk of KFD (adjusted hazard ratio [aHR] 1.52; 95% CI: 1.22‐1.89). aHRs for KFD were 1.17 (95% CI: 0.89‐1.53), 2.21 (95% CI: 1.59‐3.08), and 2.20 (95% CI: 1.55‐3.11) for metabolically healthy obesity with BMI 30 to 34.9, BMI 35 to 39.9, and BMI ≥ 40 kg/m 2 . These associations were consistent among men and women, patients with eGFR ≥ or < 90 mL/min/1.73 m 2, and age ≥ or < 55 years. The risk of KFD was highest among metabolically unhealthy individuals with BMI ≥ 40 (aHR 4.02; 95% CI: 3.40‐4.75 vs. metabolically healthy individuals with normal weight). Conclusions: Obesity, whether in the presence or absence of metabolic health, is a risk factor for KFD.